Nineteenth Century Weight in the United States: Revaluating Net Nutrition during Economic Development - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2015)
Heights and body mass index values (BMIs) are now well accepted measures that reflect net nutrition during economic development and institutional change. This study uses 19th century weights instead of BMIs to measure factors associated with current net nutrition. Across the weight distribution and throughout the 19th century, white and black average weights decreased by 8.5 and 6.3 percent, respectively. Farmers and unskilled workers had positive weight returns associated with rural agricultural lifestyles. Weights in the Deep South were greater than other regions within the US, indicating that while Southern infectious disease rates were high, Southern current net nutrition was better than elsewhere within the US.
Keywords: I10; J11; J71; N31; 330; weight; biological measurements; 19th century health; quantile estimation